Nickel-iron-manganese carbonate ternary precursor and preparation method thereof

Through the two-stage synthesis method of nickel ferromanganese carbonate ternary precursor, a material with high spherical shape and mesh microporous structure is generated, which solves the complex and cost of synthesis of existing carbonate precursors, and improves the electrochemical performance of the cathode material of sodium ion battery.

CN119528231AInactive Publication Date: 2025-02-28ANHUI HANRUI NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411721200.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing carbonate precursor synthesis process is complex, the cost is high, the core mesh skeleton is not obvious, and the micropore structure is not easy to regulate, which leads to prone to cracking and collapse when used, affecting electrical performance.

Method used

The ternary precursor of nickel ferromanganese carbonate is adopted to pass a two-stage synthesis method: the first stage is to generate the core under high temperature, low stirring speed and low pH conditions, and the second stage is to grow the shell under high pH and stirring speed conditions to form a structure that is loose inside and solid outside.

Benefits of technology

The ternary precursor material with high spherical and mesh microporous structure is achieved, which simplifies the synthesis process, reduces costs, and improves the structural stability and electrochemical performance of the positive electrode material of sodium ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528231A_ABST
    Figure CN119528231A_ABST
Patent Text Reader

Abstract

The invention provides a nickel-iron-manganese carbonate ternary precursor and a preparation method thereof, the chemical formula of the precursor is NixFeyMnzCO3, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1, more preferably, x is more than or equal to 0.3 and less than or equal to 0.4, y is more than or equal to 0.2 and less than or equal to 0.4, and z is more than or equal to 0.3 and less than or equal to 0.4. The inner core and the shell of the prepared precursor are both carbonate, the inner core is of a sheet-shaped blocked net-shaped micropore structure, the shell is formed by stacking compact primary particles, and the whole precursor has the structural characteristic that the interior is loose and the exterior is solid. In the sintering process, a metal source can be promoted to quickly enter a precursor, electrolyte can be promoted to fully infiltrate the interior of the precursor at the battery end, and collapse and cracking phenomena caused by volume change can be relieved in the charging and discharging process. According to the invention, the production cost of the precursor is obviously reduced, the synthesis process is simplified, the micropore structure of the inner core can be regulated and controlled, and the performance of the positive electrode material in the aspects of capacity, circulation and the like is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrode material technology, and more specifically, relates to a nickel-iron-manganese carbonate ternary precursor and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are highly favored in new energy vehicles, mobile phones and other fields due to their high energy density, operating voltage, safety performance and other advantages. However, due to the limited reserves of lithium metal in the world and the high price of lithium, the production cost of lithium-ion batteries remains high. Compared with sodium-ion batteries, not only are the working principles and production processes highly overlapping, but also the sodium resources are abundant, easy to mine and low in cost. Therefore, compared with lithium-ion batteries, sodium-ion batteries have more cost advantages. Compared with the sodium battery precursors prepared by the hydroxide system, the carbonate system products not only have regular morphology, high sphericity, and high tap density, but can also further control production costs.

[0003] The existing carbonate precursor synthesis process is complicated, the synthetic product is dense, and cracks or even hollow collapse are easily generated at the battery end, which has an adverse effect on the electrical performance. CN116947119A discloses a method of using a coprecipitation method to control the different ratios of hydroxide and carbonate in its core and shell by adjusting the pH value, thereby obtaining basic carbonate precursor particles with different densities of the core and shell to alleviate the occurrence of the above problems. However, its core is synthesized under high pH conditions, the hydroxide content is high, and only a small area of ​​the network skeleton is formed. The coexistence of the basic carbonate precursor carbonate and hydroxide phase products synthesized by this process often promotes the occurrence of side reactions, which has an adverse effect on the electrical performance. At the same time, the core is small, the network structure is not obvious, the microporous structure is poorly controllable, the production process is complex, and the difficulty coefficient of regulation is high. Summary of the invention

[0004] The purpose of the present application is to provide a nickel-iron-manganese carbonate ternary precursor, aiming to solve the technical problems existing in the prior art that the synthesis process of the basic carbonate precursor is complicated, the cost is high, the inner core network skeleton is not obvious, the microporous structure is not easy to further regulate, and the carbonate precursor particles are too dense, which is easy to crack and collapse when used in sodium ion batteries, resulting in poor capacity and poor cycle.

[0005] To achieve the above objectives, the present application first provides a nickel-iron-manganese carbonate ternary precursor, the chemical formula of which is: NixFeyMnzCO3, wherein 0<x<1, 0<y<1, 0<z<1, x+y+z=1; more preferably, 0.3≤x≤0.4, 0.2≤y≤0.4, 0.3≤z≤0.4.

[0006] The crystal structure of the precursor includes an inner core and an outer shell covering the inner core, and both the inner core and the outer shell are carbonates containing nickel, iron and manganese; the inner core has a mesh microporous structure with sheet barriers, and the outer shell is formed by dense stacking of primary particles, and the D50 particle size of the nickel-iron-manganese carbonate ternary precursor is 2μm-15μm.

[0007] The applicant has found through research that a core diameter that is too large or too small will lead to a decrease in the strength of the precursor particles and an unclear core network structure, which will increase side reactions and reduce the ion transmission efficiency, thereby adversely affecting the electrical properties of the positive electrode material. Based on a large number of studies and tests, the core diameter is preferably 1 μm-5 μm, the shell thickness is 1 μm-10 μm, and the ratio of the inner shell thickness to the outer core thickness is 0.8:(1-2).

[0008] It should be noted that the thickness of the inner region refers to the length from the core to the surface of the inner region; the thickness of the outer region refers to the length from the surface of the inner region to the surface of the outer region.

[0009] Secondly, the present application provides a preparation method of the above-mentioned nickel iron manganese carbonate ternary precursor, and the precursor synthesis process mainly includes two stages, the first stage is seed synthesis, and the second stage is crystal growth. First, the salt solution and the carbonate solution are added to the bottom liquid containing the organic complexing agent at a uniform speed under stirring conditions, and the nickel iron manganese carbonate ternary precursor crystal seeds are generated under high synthesis temperature, low stirring speed, salt solution inlet and pH conditions. Low pH in the process reduces the supersaturation of the reaction process, promotes the precursor growth process under the action of high synthesis temperature, and the low salt solution inlet can reduce the number of nuclei during the reaction, and can reduce the number of particle collisions at low stirring speeds, which helps to promote the rapid growth of seed particles to form a loose and porous structure, and the introduction of organic complexes can not only promote the directional growth of ternary precursor seeds, but also accumulate a mesh microporous structure with a sheet barrier, and the change of its content can further regulate the size and density of the mesh microporous structure. Then, the seed crystal is used as the core to grow the precursor crystal. This stage is carried out under the combined action of a high pH, ​​stirring speed and an ammonium-containing complexing agent, which inhibits the rapid growth of the grains and generates a shell with a dense structure formed by stacking primary particles on the surface of the core, and finally the ternary precursor particles are obtained. The above preparation method specifically comprises the following steps: S01: Seed crystal preparation stage: The prepared nickel iron manganese metal salt solution and carbonate precipitant solution are added to a reaction kettle containing an organic complexing agent as a base liquid at a uniform speed under stirring conditions to prepare nickel iron manganese carbonate ternary precursor seed crystals until the particle size of the nickel iron manganese carbonate ternary precursor seed crystals reaches 1-5 μm, thereby obtaining the desired seed crystal slurry; S02: Crystal growth stage: Use the prepared ammonium complexing agent solution and carbonate solution to adjust the ammonia mass concentration and pH of the seed slurry prepared in step S01 to 1.0-3.0 g / L and 7.0-8.0 respectively, then add the same nickel-iron-manganese metal salt solution and carbonate solution and the ammonium complexing agent solution as in step S01 into the reactor at a uniform speed under stirring conditions, and carry out the growth reaction of the nickel-iron-manganese carbonate ternary precursor until the crystal size of the ternary precursor reaches 2-15 μm, thereby obtaining the required nickel-iron-manganese carbonate ternary precursor slurry; S03: Synthetic product processing: The precursor slurry obtained in S02 is subjected to solid-liquid separation, washing, and drying treatment to obtain a nickel-iron-manganese carbonate ternary precursor.

[0010] In step S01, the nickel salt in the metal salt solution is at least one of nickel sulfate, nickel chloride, and nickel nitrate; the iron salt is at least one of ferrous sulfate, ferrous chloride, and ferrous nitrate; the manganese salt is at least one of manganese sulfate, manganese chloride, and manganese nitrate; the carbonate is Na2CO3; and the organic complexing agent is citric acid. In addition, experiments have found that the microporous structure of the inner core can be further regulated by controlling the content of the organic complexing agent citric acid in S01.

[0011] The relevant reaction principle of step S01 is: the nickel-iron-manganese metal salt solution and the carbonate are contacted to form nuclei at the moment, and the organic complexing agent citric acid as the base liquid in the nucleation process can complex some ions, on the one hand, to regulate the nucleation rate and grain growth rate, and on the other hand, to induce the directional growth reaction of the nickel-iron-manganese carbonate ternary precursor crystal seeds. At this time, the lower liquid intake ensures that there are fewer nuclei in the early stage of synthesis, and the possibility of collision of the early nucleation particles is significantly reduced at a low stirring speed. At the same time, with a lower pH, the growth rate of the precursor is significantly increased, thereby quickly accumulating a nickel-iron-manganese carbonate ternary precursor core with a honeycomb structure with a thin sheet barrier.

[0012] In addition, citric acid is introduced as a weak acid, which also has a certain reducing property and can further inhibit Fe 2+ Oxidized to Fe 3+ , preventing the precipitation of insoluble oxides and achieving coprecipitation of various metal ions. Thus, the microporous structure of the prepared core flake barrier is more obvious and clear. In addition, repeated experiments have found that the addition of citric acid can effectively reduce the size of nucleation grains and has a refinement effect on the microporous structure of the core. Within a certain content range, as the citric acid content increases, the internal micropore density increases and the pore size decreases. This may be related to the stronger complexing ability and special properties of citric acid.

[0013] The stirring speed, the amount of salt solution inlet, and the pH value of step S01 are lower than those of step S02, and the temperature is higher than that of step S02. The stirring speed and the amount of salt solution in step S01 shall not be lower than 1 / 2 of those of step S02; the temperature shall not be higher than 2 times that of step S02, and the difference in pH value shall not be less than 2 but not more than 3.

[0014] The reaction conditions in step S01 are as follows: The concentration of nickel-iron-manganese metal salt solution is 1.2-2 mol / L, where the molar ratio of nickel, iron and manganese is (30-40): (20-40): (30-40). The concentration of sodium carbonate solution is 200-250 g / L The mass concentration of citric acid as the organic complexing agent of the base liquid is 1.0-3.0g / L The reaction temperature of the reaction system is 60°C-80°C; The flow rate of salt solution inlet is 2L / h-4L / h; the flow rate of alkali solution inlet is 2L / h-4L / h; The stirring speed is 300rpm-400rpm; The pH of the reaction system is controlled at 5.0-6.0; In step S02, ammonium sulfate is used as a complexing agent. The internal ammonium ions can promote the simultaneous and homogeneous precipitation of nickel ions, iron ions and manganese ions, thereby improving the sphericity and tap density of the product and forming a dense shell.

[0015] The reaction conditions of step S02 are: The concentration of nickel-iron-manganese metal salt solution is 1.2-2 mol / L, where the molar ratio of nickel, iron and manganese is (30-40): (20-40): (30-40). The concentration of sodium carbonate solution is 200-250 g / L, and the concentration of complexing agent ammonium sulfate solution is 110 g / L During the reaction, the flow rate of the salt solution is 4L / h-8L / h, the flow rate of the alkali solution is 8L / h-16L / h; the flow rate of the complexing agent solution is 0.3L / h-2.5L / h The pH of the reaction system is 7.0-8.0; The amount of ammonia-containing complexing agent fed into the reaction process must be such that the ammonia mass concentration of the reaction system is controlled at 1-3 g / L; The reaction temperature of the reaction system is 30°C-40°C; The stirring speed is 600rpm-800rpm; The drying temperature in step S03 is 90-120° C. and the drying time is 10-16 hours.

[0016] In both steps S01 and S02, sodium carbonate solution is used as a precipitant.

[0017] The present application can also be applied to a sodium ion battery positive electrode material, the raw materials of which include the ternary precursor.

[0018] The present application can also be applied to a sodium ion battery, the raw materials of which include the sodium ion battery positive electrode material.

[0019] This application has the following advantages: 1 Compared with the nickel-iron-manganese basic carbonate and nickel-iron-manganese hydroxide precursors synthesized by the prior art, the present application provides a nickel-iron-manganese carbonate ternary precursor material with high sphericity, in which both the inner and outer cores are carbonates, and the inner core has an obvious reticular microporous skeleton, and the reticular structure can be further regulated. The synthesis process is simple, which effectively reduces the material production cost, has high economic benefits, and is suitable for industrial promotion.

[0020] 2. The inner core and outer core of the nickel-iron-manganese carbonate ternary precursor involved in this application are both carbonates containing nickel, iron, and manganese. The inner core is a mesh microporous structure with sheet barriers, and the outer shell has a high density. When used to prepare nickel-iron-manganese positive electrode materials for sodium ion batteries, the internal mesh structure is not only conducive to promoting the rapid entry of metal sources into the precursor during the sintering process, thereby improving the uniformity of doping and mixing, but also can effectively alleviate the formation of internal microcracks and even hollow collapse caused by the large shrinkage ratio of carbonate products during sintering. The external dense shell ensures the tap density and physical strength of the precursor particles, so that the nickel-iron-manganese positive electrode material has better structural stability, and thus can improve the electrochemical performance of the positive electrode material in terms of capacity and cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0022] Figure 1 This is an electron microscope image of the surface of the ternary precursor obtained in Example 1; Figure 2 This is the electron microscope image of the core of the ternary precursor obtained in Example 1 Figure 3 This is a cross-sectional electron micrograph of the ternary precursor obtained in Example 1; Figure 4 This is a surface electron microscope image of the ternary precursor obtained in Example 3; Figure 5 This is a cross-sectional electron micrograph of the ternary precursor obtained in Example 3; Figure 6 This is an electron microscope image of the inner core of the ternary precursor obtained in Comparative Example 1; Figure 7 This is an electron microscope image of the cross section of the ternary precursor obtained in Comparative Example 1; Figure 8 This is an electron micrograph of the inner core of the ternary precursor obtained in Comparative Example 2; Fig. 9 This is an electron microscope image of the cross section of the ternary precursor obtained in Comparative Example 2; Fig.10 This is a cross-sectional electron micrograph of the ternary precursor obtained in Comparative Example 3; DETAILED DESCRIPTION

[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Example 1

[0025] S01: According to the total molar amount of nickel, iron and manganese, the required raw materials of nickel sulfate, ferrous sulfate and manganese sulfate are weighed according to the molar ratio of nickel, iron and manganese elements of 40:20:40, and the raw materials are mixed to obtain the salt solution required for the experiment, and 220g / L Na2CO3 solution is configured as the alkali solution. A citric acid solution with a mass concentration of 1g / L is configured as the base liquid. Before starting the kettle, the pH of the base liquid is adjusted to 5.0-5.2, and then the peristaltic pump is used to feed at a uniform speed. At the same time, the salt solution and the alkali solution are transported to the reactor containing the base liquid for the precursor synthesis experiment. During the synthesis process, the temperature of the reaction system is 60°C, the stirring speed is 300rpm, the flow rate of the salt solution is controlled at 2L / h, and the liquid inlet of the alkali solution is controlled at 2L / h. The pH of the synthesis process is always maintained at 5.0-5.2, and the seed solution is obtained when the seed in the reactor reaches a particle size of D50=3.0μm.

[0026] S02: Prepare 110g / L ammonium sulfate solution as a complexing agent solution for standby use, use ammonium sulfate solution to adjust the ammonia mass concentration of the seed solution to 1.0-1.5g / L, and then adjust the pH of the seed solution to 7.0-7.2, then the salt solution, alkali solution and ammonium sulfate solution prepared in S01 are simultaneously fed to the reactor by a peristaltic pump at a uniform speed for crystal growth reaction, the temperature of the reaction system is controlled at 30°C, the free ammonia mass concentration in the solution is 1.0-1.5g / L, the stirring speed is 600rpm, wherein the flow rate of the salt solution is 4L / h, the flow rate of the alkali solution is 8L / h, and the flow rate of ammonium sulfate is 0.5L / h, and the pH of the synthesis process is always controlled to be maintained at 7.0-7.2, and the precursor particles in the reactor reach the target particle size, stop feeding, and obtain precursor slurry.

[0027] S03: The precursor slurry is filtered, washed, dried, sieved, demagnetized and packaged to obtain the nickel iron manganese carbonate ternary precursor Ni 0.4 Fe 0.2 Mn 0.4 CO3, the particle size D50 of the obtained nickel-iron-manganese carbonate ternary precursor is 11.1 μm and the tap density is 1.59 g / cm 3 , specific surface area is 54.3m 2 / g. Example 2

[0028] S01: According to the total molar amount of nickel, iron and manganese, 1.6 mol / L, and the molar ratio of nickel, iron and manganese, 33:33:34, the required raw materials of nickel sulfate, ferrous sulfate and manganese sulfate were weighed, and the raw materials were mixed to obtain the salt solution required for the experiment, and 250 g / L of Na2CO3 solution was prepared as the alkali solution. A citric acid solution with a mass concentration of 3 g / L was prepared as the base liquid. Before starting the kettle, the pH of the base liquid was adjusted to 5.4-5.6, and then the peristaltic pump was used to feed the material at a uniform speed. At the same time, the salt solution and the alkali solution were transported to the reactor containing the base liquid for the precursor synthesis experiment. During the synthesis process, the temperature of the reaction system was 70 ° C, the stirring speed was 350 rpm, the flow rate of the salt solution was controlled at 3 L / h, and the liquid inlet of the alkali solution was controlled at 3 L / h. The pH of the synthesis process was always maintained at 5.4-5.6, and the seed solution was obtained until the seed in the reactor reached a particle size of D50 = 3.2 μm.

[0029] S02: Prepare 110g / L ammonium sulfate solution as a complexing agent solution for standby use, use ammonium sulfate solution to adjust the ammonia mass concentration of the seed solution to 2.0-2.5g / L, and then adjust the pH of the seed solution to 7.4-7.6, then the salt solution, alkali solution and ammonium sulfate solution prepared in S01 are simultaneously fed to the reactor by a peristaltic pump at a uniform speed for crystal growth reaction, the temperature of the reaction system is controlled at 35°C, the pH is 7.4-7.6, the free ammonia mass concentration in the solution is 2.0-2.5g / L, the stirring speed is 700rpm, wherein the flow rate of the mixed solution of nickel salt, iron salt and manganese salt is 6L / h, the flow rate of alkali solution is 12L / h, and the flow rate of ammonium sulfate is 1.3L / h, and the pH of the synthesis process is always controlled to be maintained at 7.4-7.6. When the precursor particles in the reactor reach the target particle size, the feeding is stopped to obtain a precursor slurry.

[0030] S03: The precursor slurry is filtered, washed, dried, sieved, demagnetized and packaged to obtain the nickel iron manganese carbonate ternary precursor Ni 0.33 Fe 0.33 Mn 0.34CO3, the particle size D50 of the obtained nickel-iron-manganese carbonate ternary precursor is 11.3 μm and the tap density is 1.53 g / cm 3 , specific surface area is 47.3m 2 / g. Example 3

[0031] S01: According to the total molar amount of nickel, iron and manganese, the required raw materials of nickel sulfate, ferrous sulfate and manganese sulfate are weighed according to the molar ratio of nickel, iron and manganese elements of 30:40:30, and the raw materials are mixed to obtain the salt solution required for the experiment, and 200g / L Na2CO3 solution is prepared as the alkali solution. A citric acid solution with a mass concentration of 2g / L is prepared as the base liquid. Before starting the kettle, the pH of the base liquid is adjusted to 5.8-6.0, and then the peristaltic pump is used to feed at a uniform speed. At the same time, the salt solution and the alkali solution are transported to the reactor containing the base liquid for the precursor synthesis experiment. During the synthesis process, the temperature of the reaction system is 80°C, the pH is always maintained at 5.8-6.0, the stirring speed is 400rpm, the flow rate of the salt solution is controlled at 4L / h, and the liquid inlet of the alkali solution is controlled at 4L / h. The seed solution is obtained when the seed in the reactor reaches a particle size of D50=3.2um.

[0032] S02: Prepare 110g / L ammonium sulfate solution as a complexing agent for standby use, use ammonium sulfate solution to adjust the ammonia mass concentration of the seed solution to 2.5-3.0g / L, and then adjust the pH of the seed solution to 7.8-8.0, then the salt solution, sodium carbonate solution and ammonium sulfate solution prepared in S01 are simultaneously fed to the reactor by a peristaltic pump at a uniform speed for crystal growth reaction, control the temperature of the reaction system at 40°C, the pH at 7.8-8.0, the free ammonia concentration in the solution at 2.5-3.0g / L, the stirring speed at 800rpm, wherein the flow rate of the mixed solution of nickel salt, iron salt and manganese salt is 8L / h, the liquid inlet amount of the alkali solution is controlled at 16L / h, the flow rate of ammonium sulfate is 2.2L / h, and the precursor particles in the reactor reach the target particle size, stop feeding, and obtain precursor slurry.

[0033] S03: The precursor slurry is filtered, washed, dried, sieved, demagnetized and packaged to obtain the nickel iron manganese carbonate ternary precursor Ni 0.30 Fe 0.40 Mn 0.30 CO3, the particle size D50 of the obtained nickel-iron-manganese carbonate ternary precursor is 12.1 μm and the tap density is 1.68 g / cm 3 , specific surface area is 51.0m 2 / g.

[0034] Figure 1 and Figure 4 Surface electron microscopy images of the carbonate ternary precursors obtained in Example 1 and Example 3, Figure 2 This is a scan of the carbonate core obtained in Example 1. Figure 1 and Figure 4 It can be seen that the obtained precursor particles are uniform, have a high degree of sphericity, and present a regular spherical or quasi-spherical shape as a whole. Figure 2 It can be seen that the core of the prepared precursor is loose and porous, and the surface presents a microporous structure with flake barriers.

[0035] Figure 3 , Figure 5 The cross-sectional electron micrographs of the ternary precursors prepared in Example 1 and Example 3 show that the inner core of the prepared nickel-iron-manganese carbonate ternary precursor particles presents a reticular microporous structure with sheet-like barriers, and the outer shell is composed of dense primary particles stacked. The overall structure is loose inside and solid outside. The morphology of the inner core and outer core of the precursor shown in the cross-sectional electron micrograph is consistent with the scanning electron micrographs of the inner and outer cores.

[0036] Comparative Example 1 The preparation method of the nickel-iron-manganese carbonate ternary precursor in this comparative example is basically the same as that in Example 1, except that in step S01: the base liquid does not use citric acid, but only water with the same volume and pH as S01. The particle size D50 of the obtained nickel-iron-manganese carbonate ternary precursor is 12.3 μm and the tap density is 1.67 g / cm 3 , specific surface area is 48.3m 2 / g.

[0037] Comparative Example 2 The preparation method of the nickel-iron-manganese carbonate ternary precursor in this comparative example is basically the same as that in Example 1, except that in step S01: the mass concentration of citric acid in the base solution is increased to 3 g / L. The particle size D50 of the obtained nickel-iron-manganese carbonate ternary precursor is 10.2 μm and the tap density is 1.61 g / cm 3 , specific surface area is 50.1m 2 / g.

[0038] Figure 6 and Figure 7 They are the core and cross-section electron microscopy images of the precursor obtained in Comparative Example 1, Figure 6 It can be seen that when the base liquid does not contain citric acid, the obtained precursor core flaky structure characteristics are not obvious, the looseness decreases, a hard shell similar to an oxide appears on the surface, and even some elements are segregated. Figure 7 It can be found that the spherical core of the nickel-iron-manganese ternary precursor obtained in Comparative Example 1 still maintains a relatively dense state, the lamellar structure is not obvious, and only a small amount of micropores appear. It can be seen that citric acid is extremely important for preparing a precursor with a network structure with a lamellar barrier as the core.

[0039] Figure 8 and Fig. 9 They are the core and cross-sectional electron microscope images of the precursor obtained in comparative example 2, respectively. It can be found from the figure that the core of the prepared precursor is a microporous structure formed by thin flake barriers, the holes are reduced and the density is significantly improved. The study found that the presence of citric acid not only has a huge effect on the formation of the porous structure of the core, but also has a refining effect on the grains and core of the reactor, and then regulates the density of the network structure and the size of the holes. Within a certain content range, as the citric acid content increases, the micropores of the core decrease and the density increases. In combination with Example 1 and comparative example 1, it is found that when the synthesis process is the same, the core network structure, flake morphology and hole size obtained by the flake barrier of the precursor obtained under different citric acid contents in the base liquid have significant differences. When the citric acid content is 1g / L, the core flakes obtained have a significant growth trend, the holes obtained by the barrier are large, and the looseness is high. When the citric acid content is 3g / L, the flakes are fine, the holes obtained by the barrier are small, and the structure is dense.

[0040] Comparative Example 3 The preparation method of the nickel iron manganese carbonate ternary precursor in this comparative example is basically the same as that in Example 1, except that the entire synthesis process is synthesized using the S02 process. The S01 step is not included. The particle size D50 of the obtained nickel iron manganese carbonate ternary precursor is 10.2 μm and the tap density is 1.70 g / cm 3 , specific surface area is 41.2m 2 / g.

[0041] from Fig.10 It can be seen that the nickel-iron-manganese carbonate ternary precursor obtained in Comparative Example 2 is a conventional particle, and the spherical core of the nickel-iron-manganese ternary precursor does not form a three-dimensional network structure.

[0042] Performance Test: The nickel-iron-manganese carbonate ternary precursors prepared in the above Examples 1-3 and Comparative Examples 1-3 were sintered with a sodium source to prepare button cells, and the electrochemical performance was tested.

[0043] The precursor materials synthesized under different synthesis conditions were tested at room temperature (25°C) at 2.0-4.V. The test results are shown in Table 1: The test results show that the discharge capacity at 0.2C, 0.5C, and 1C, the first coulombic efficiency at 0.2C, and the 50-cycle retention rate at 1C of Example 1 are all higher than those of Comparative Example 3, wherein the discharge capacity at 0.2C, the first coulombic efficiency, and the 50-cycle retention rate at 1C of Example 1 are 151.3 mAh / g, 92.3%, and 90.3%, respectively, which are much higher than 140.4 mAh / g, 86.4%, and 82.5% of Comparative Example 3, which indicates that regulating the crystal structure of the precursor helps to improve the electrochemical performance of the positive electrode material. In addition, it can be seen from the test results of Comparative Example 1 vs. 2 and Example 1 that regulating the microporous structure of the inner core using citric acid helps to further improve the capacity and cycle performance of the precursor. It can be seen that the nickel-iron-manganese carbonate ternary precursor material prepared by the present invention, which is loose inside and solid outside, is applied to sodium ion batteries and has obvious help in improving their capacity and cycle performance.

[0044] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A nickel-iron-manganese carbonate ternary precursor, characterized in that Its chemical formula is: NixFeyMnzCO3, wherein 0<x<1, 0<y<1, 0<z<1, x+y+z=1, and more preferably, 0.3≤x≤0.4, 0.2≤y≤0.4, and 0.3≤z≤0.

4.

2. The nickel-iron-manganese carbonate ternary precursor according to claim 1, characterized in that: The crystal structure of the precursor includes an inner core and an outer shell covering the inner core, and both the inner core and the outer shell are carbonates containing nickel, iron and manganese; the inner core has a mesh microporous structure with sheet barriers, and the outer shell is formed by dense stacking of primary particles, and the D50 particle size of the nickel-iron-manganese carbonate ternary precursor is 2μm-15μm.

3. The nickel-iron-manganese carbonate ternary precursor according to claim 2, characterized in that: The diameter of the inner core is 1 μm-5 μm, the thickness of the outer shell is 1 μm-10 μm, and the ratio of the thickness of the inner shell to the thickness of the outer core is 0.8:(1-2).

4. The method for preparing the nickel-iron-manganese carbonate ternary precursor according to any one of claims 1 to 3, characterized in that: The following steps are involved: S01: Seed crystal preparation stage: nickel iron manganese metal salt solution and carbonate precipitant solution are added to a reaction kettle containing an organic complexing agent as a base liquid at a uniform speed under stirring conditions to prepare nickel iron manganese carbonate ternary precursor seed crystals until the particle size of the nickel iron manganese carbonate ternary precursor seed crystals reaches 1-5 μm, thereby obtaining the desired seed crystal slurry; S02: Crystal growth stage: using an ammonium complexing agent solution and a carbonate solution to adjust the ammonia mass concentration and pH of the seed slurry prepared in step S01 to 1.0-3.0 g / L and 7.0-8.0, respectively, and then adding the same nickel-iron-manganese metal salt solution and carbonate solution and the ammonium complexing agent solution as in step S01 to the reactor at a uniform speed under stirring conditions, and performing a growth reaction of a nickel-iron-manganese carbonate ternary precursor until the crystal size of the ternary precursor reaches 2-15 μm, thereby obtaining the required nickel-iron-manganese carbonate ternary precursor slurry; S03: Synthetic product processing: The precursor slurry obtained in S02 is subjected to solid-liquid separation, washing, and drying to obtain a nickel-iron-manganese carbonate ternary precursor.

5. The method for preparing the nickel-iron-manganese carbonate ternary precursor according to claim 4, characterized in that: In step S01, the nickel salt in the metal salt solution is at least one of nickel sulfate, nickel chloride, and nickel nitrate; the iron salt is at least one of ferrous sulfate, ferrous chloride, and ferrous nitrate; the manganese salt is at least one of manganese sulfate, manganese chloride, and manganese nitrate; the carbonate is Na2CO3; and the organic complexing agent is citric acid.

6. The method for preparing the nickel-iron-manganese carbonate ternary precursor according to claim 4, characterized in that: The stirring speed, salt solution inlet volume and pH value of step S01 are lower than those of step S02, and the temperature is higher than that of step S02; wherein, the stirring speed and salt solution inlet volume of step S01 shall not be lower than 1 / 2 of those of step S02; the temperature shall not be higher than 2 times that of step S02, and the pH difference shall not be less than 2 but not more than 3.

7. The method for preparing the nickel-iron-manganese carbonate ternary precursor according to claim 4, characterized in that: Step S01 reaction conditions are as follows: The molar concentration of the nickel-iron-manganese metal salt solution is 1.2-2 mol / L, wherein the molar ratio of nickel element, iron element and manganese element is (30-40): (20-40): (30-40), and the concentration of the carbonate solution is 200-250 g / L; The mass concentration of citric acid, an organic complexing agent used as the base solution, is 1.0-3.0 g / L; The reaction temperature of the reaction system is 60°C-80°C; The flow rate of salt solution inlet is 2L / h-4L / h; the flow rate of alkali solution inlet is 2L / h-4L / h The stirring speed is 300rpm-400rpm; The pH of the reaction system was controlled at 5.0-6.

0.

8. The method for preparing the nickel-iron-manganese carbonate ternary precursor according to claim 4, characterized in that: In step S02, the ammonium-containing complexing agent is ammonium sulfate.

9. The method for preparing the nickel-iron-manganese carbonate ternary precursor according to claim 4, characterized in that: The reaction conditions of step S02 are as follows: The molar concentration of nickel-iron-manganese metal salt solution is 1.2-2 mol / L, wherein the molar ratio of nickel element, iron element and manganese element is (30-40): (20-40): (30-40), the concentration of alkali carbonate solution is 200-250 g / L; the concentration of complexing agent ammonium sulfate solution is 110 g / L; The mass concentration of free ammonia in the reaction system is 1.0 g / L-3.0 g / L; The reaction temperature of the reaction system is 30°C-40°C; The flow rate of salt solution inlet is 4L / h-8L / h; the flow rate of alkali solution inlet is 8L / h-16L / h; the flow rate of complexing agent solution inlet is 0.3L / h-2.5L / h; The stirring speed is 600rpm-800rpm; The pH of the reaction system was controlled at 7.0-8.

0.

10. The method for preparing the nickel-iron-manganese carbonate ternary precursor according to claim 4, characterized in that: The drying temperature in step S03 is 90-120° C. and the drying time is 10-16 hours.

Citation Information

Patent Citations

  • Nickel-iron-manganese positive electrode material precursor, preparation method of nickel-iron-manganese positive electrode material precursor, positive electrode material and sodium ion battery

    CN116947119A